Effect of moringa oleifera leaf powder and egg supplementation on weight gain and hemoglobinin undernourished children aged 36-59 months - Hawa Lessy; Etika Ratna Noer; Ahmad Syauqy; Diana Nur Afifah (AcTion: Aceh Nutrition Journal, 2026)
Malnutrition and anemia remain major public health challenges among children under the age of five, adversely affecting their growth and overall health. In East Nusa Tenggara Province, particularly in South Central Timor, these conditions are prevalent. Moringa oleifera leaves are rich in protein, iron, and essential micronutrients, suggesting their potential as a local food-based intervention. This study aimed to evaluate the effect of Moringa leaf powder combined with egg consumption on weight gain and hemoglobin levels in undernourished children aged 36–59 months at the Batuputih Health Center, South Central Timor, from March to May 2025. A quasi-experimental pre–post test with a control group design was conducted with 40 children, divided equally into an intervention group (15 g/day moringa leaf powder + 1 egg) and a control group (1 egg) for 60 days. Paired and independent t-tests were used, with significance set at p<0.05. The results demonstrated significant weight gain in both groups (p<0.001), with a greater increase in the intervention group (p=0.001). Height and hemoglobin levels increased within groups (p=0.596; p=0.225) but did not differ significantly between the groups. In conclusion, daily supplementation with Moringa leaf powder and eggs for 60 days effectively enhanced body weight but did not significantly affect height or hemoglobin levels in undernourished children.